Determinants of the EU sustainable development policy effectiveness: DEA approach - Janusz Rosiek (Economic and Environmental Studies (E&ES), 2016)
In the last decades, sustainable development has become one of the key principles in the European Union policies. Its concept is based three pillars: economic, social and environmental. They are interdependent and mutually reinforcing. Europe 2020 strategy stresses the importance of more sustainable EU development by establishing a long-term approach based on a clear guidance to climate and energy change. The overall aim of the renewed EU Sustainable Development Strategy (SDS) is to identify and develop activity to ensure the EU to achieve continuous improvement of quality of life through the creation of sustainable communities able to manage and use resources efficiently. It should be based mainly on social innovation potential of the EU economy, to form the background for: economic development, social cohesion and environmental protection. The main goal of publication is to estimate the EU sustainable development policy impact on the economies of the EU Member States. Analysis will be based on Data Envelopment Analysis (DEA) approach, which will let determine the efficiency of this policy. It should contribute to better understanding of the ongoing processes of the sustainable development, providing possibility for monitoring, forecasting and estimating the impact of particular factors on the EU economy in terms of economic, social and environmental aspects.
Keywords: O43; O44; 330; sustainable development; effectiveness of the sustainable development policy; DEA approach